Review on Integrated On-Board Charger-Traction Systems: V2G Topologies, Control Approaches, Standards and Power Density State-of-the-Art for Electric Vehicle - Shahid Jaman; Sajib Chakraborty; Dai-Duong Tran; Thomas Geury; Mohamed El Baghdadi; Omar Hegazy (Energies, 2022)
This article reviews the different topologies compatible with V2G feature and control approaches of integrated onboard charger (iOBC) systems for battery electric vehicles (BEVs). The integrated topologies are presented, analyzed, and compared in terms of component count, switching frequency, total harmonic distortion (THD), charging and traction efficiencies, controllability, reliability and multifunctionality. This paper also analyzes different control approaches for charging and traction modes. Moreover, the performance indices such as setting time, rise time, overshoot, etc., are summarized for charging and traction operations. Additionally, the feasibility of a Level 3 charging (AC fast charging with 400 Vac) of up to 44 kW iOBC is discussed in terms of converter efficiencies with different switching frequencies and switch technologies such as SiC and GaN. Finally, this paper explores the power density trends of different commercial integrated charging systems. The power density trend analysis could certainly help researchers and solution engineers in the automotive industry to select the suitable converter topology to achieve the projected power density.